DAGESTAN MANUSCRIPTS IN FOREIGN COLLECTIONS (KORNELI KEKELIDZE NATIONAL CENTRE OF MANUSCRIPTS) - Sihsaidov, Amri Rzaevic; Tagirova, Natal'a Amrievna (History, Archeology and Ethnography of the Caucasus, 2018)
This article is the first experience in the series "Dagestan manuscripts in foreign collections" and is devoted to Dagestan materials stored in the Institute of manuscripts of the Academy of Sciences of Georgia. These materials are presented as texts received in Dagestan from the Middle East, and the works of the actual local authors who wrote in Arabic. The collection is characterized by a variety of genres, including manuscripts on grammar, Muslim law, Sufism, dogma, logic, history and other disciplines published in the "Catalogue of Arabic manuscripts" of the Institute of Manuscripts. K. S. Kekelidze of Georgian Academy of Sciences.